Thermal insulation materials for building applications - Latif, Eshrar; Bevan, Rachel; Woolley, Tom (ICE Publishing, 2019)
Modern day buildings are expected to be low energy or near zero energy to reduce carbon emissions. A key step in making building low energy is to minimise heat transfer through the building fabric with insulation fabrics. However, how can a practitioner choose the most effective fabric for the job in hand? With so many thermal insulation materials on the market and each making claims associated with their performance, it is difficult for a specifier, contractor or an end user to select the insulation material most appropriate for a specific building project. Thermal Insulation Materials for Building Applications aims to address that problem. This book presents the variations, technical details and capabilities of state-of-the-art thermal insulation materials for building applications.